Penerapan Pembelajaran Model Kooperatif Tipe TAI (Team Assisted Individualization) untuk Meningkatkan Kreativitas dan Prestasi Belajar Matematika Siswa Kelas X MIPA - Nasrulloh, M. Farid (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2019)
This study aims to improve creativity and student achievement in learning mathematics in class X MIPA MA Bahrul Ulum Jombang. In general, this study seeks to increase creativity and student achievement by using a cooperative type TAI (Team Assisted Individualization) model.This type of research is Class Action Research (CAR). The subjects of this research were 32 students of class X MIPA MA Bahrul Ulum. The object of this research is the implementation of mathematics learning using a cooperative type TAI (Team Assisted Individualization) model. This Classroom Action Research was conducted in 2 cycles, each of which consisted of 2 meetings. Data obtained from observation sheets, field notes, student creativity questionnaires, results of student and teacher interviews, cycle tests, and documentation.The results of the study showed that using a cooperative model type TAI (Team Assisted Individualization). Can improve creativity and student achievement. Student creativity seen from all indicators of creativity has increased. In the first cycle of 58%, the second cycle was 80%. Creativity can be seen from the ability to produce a lot of ideas, the ability to express various kinds of solutions to problems, the ability to find answers, tend to give more answers, respond to questions asked, have many questions, and be able to describe things in detail. Mathematics learning achievement of students experienced an increase seen from the average cycle test score in class X MIPA MA Bahrul Ulum, from 62.74 to 79.84. Student learning achievement can be achieved from the changes in actions taken by changing previous learning. Keywords: TAI, Creativity, Learning Achievement